(3x-7)=(9x-5)

Simple and best practice solution for (3x-7)=(9x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3x-7)=(9x-5) equation:


Simplifying
(3x + -7) = (9x + -5)

Reorder the terms:
(-7 + 3x) = (9x + -5)

Remove parenthesis around (-7 + 3x)
-7 + 3x = (9x + -5)

Reorder the terms:
-7 + 3x = (-5 + 9x)

Remove parenthesis around (-5 + 9x)
-7 + 3x = -5 + 9x

Solving
-7 + 3x = -5 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
-7 + 3x + -9x = -5 + 9x + -9x

Combine like terms: 3x + -9x = -6x
-7 + -6x = -5 + 9x + -9x

Combine like terms: 9x + -9x = 0
-7 + -6x = -5 + 0
-7 + -6x = -5

Add '7' to each side of the equation.
-7 + 7 + -6x = -5 + 7

Combine like terms: -7 + 7 = 0
0 + -6x = -5 + 7
-6x = -5 + 7

Combine like terms: -5 + 7 = 2
-6x = 2

Divide each side by '-6'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| 1/2x-3=5/8x | | 7(x+3)-1=5(x+4)+10 | | 5x^2+2x-192=0 | | 2t-6=9 | | 10+y=13 | | -12x+4y=-20 | | x-5=2(4x-3) | | 2.5/10=x/12 | | -13=5(1+4m)-3 | | 13-12x=2y | | -123+12x=x+108 | | .7x-.6(60+x)=-.5(60) | | 25+10(12-x)=2x-7 | | 8=18-2g | | 4(1+2x)=7(x-5) | | -21=7x | | 248/4=93/x | | y-(-5)=9(x-(-3)) | | -4=(-4x-5) | | 7-4x=-33 | | .07(4x+10+5.30)=1.08(4x+5+8.60) | | 6c+15-5c-8= | | 2(n-3)=-2+2n | | 6=-5+r/8 | | 1.8+7n=9.5-3n | | 47=7d | | x=3y-111 | | 152/4=532/x | | 12(x-7)= | | 1.07(4x+10)+5.30=1.08(4x+5)+8.60 | | 1+0.07(4x+10)+5.30=1+0.08(4x+5)+8.60 | | 229/4=57.25 |

Equations solver categories